2006
DOI: 10.1111/j.1365-294x.2006.02874.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial evidence for distinct phylogeographic units in the endangered Malagasy poison frogMantella bernhardi

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…Further study is also necessary to assign the Mantella population of BMNP, although Rabemananjara et al (2007) have shown that Mantella baroni is a genetically very uniform species, with identical haplotypes distributed over much of its distribution area including specimens from Andringitra that show extended yellow-greenish dorsal colouration. In line with several studies indicating that the south-eastern part of Madagascar is undersampled (Raxworthy et al, 2003) and contains genetically highly divergent phylogeographic lineages (Vieites et al, 2006), our study supports the need of more intensive herpetological survey work in this region, which should be carried out in concert with taxonomic study of the encountered populations. …”
Section: Discussionsupporting
confidence: 87%
“…Further study is also necessary to assign the Mantella population of BMNP, although Rabemananjara et al (2007) have shown that Mantella baroni is a genetically very uniform species, with identical haplotypes distributed over much of its distribution area including specimens from Andringitra that show extended yellow-greenish dorsal colouration. In line with several studies indicating that the south-eastern part of Madagascar is undersampled (Raxworthy et al, 2003) and contains genetically highly divergent phylogeographic lineages (Vieites et al, 2006), our study supports the need of more intensive herpetological survey work in this region, which should be carried out in concert with taxonomic study of the encountered populations. …”
Section: Discussionsupporting
confidence: 87%
“…Although some species like Hemidactylus do not show distinctive clades in the South East, in others, like P. lineata, C. crypticum, and possibly F. lateralis, there is a clear differentiation between samples north and south of the Mananara river. The data shown here, together with studies available for several groups of vertebrates that inhabit this region in Madagascar (Goodman and Ganzhorn, 2004;Louis et al, 2005;Sterling and Ramarason, 1996;Vieites et al, 2006) make it plausible that these two east coast rivers act as barriers. More samples, particularly from localities close to the north and south banks of the Mangoro and Mananara rivers, are needed to test this hypothesis.…”
Section: Comparative Phylogeographymentioning
confidence: 61%
“…The endangered M. bernhardi occurs in two separate regions in south-east Madagascar. Cytb sequence comparisons of individuals from across the entire range confirmed the genetic separation (reciprocal monophyly) of the two groups and provided evidence of barriers to gene flow (probably rivers) predating the recent habitat destruction mediated by humans (Vieites et al, 2006).…”
Section: Zeisset and Tjc Beebeementioning
confidence: 94%